2020
DOI: 10.1155/2020/2895795
|View full text |Cite
|
Sign up to set email alerts
|

The Tonoplast Intrinsic Protein Gene KvTIP3 is Responsive to Different Abiotic Stresses in Kosteletzkya virginica

Abstract: In higher plants, aquaporin proteins (AQPs) play important roles in the uptake of water across cell membranes. However, their functions in halophytes are still largely unknown. In this work, we isolated, cloned, and identified KvTIP3, a tonoplast intrinsic protein gene from Kosteletzkya virginica. Bioinformatic analyses demonstrated that KvTIP3 encoded a tonoplast protein with the common properties of AQPs. Further multiple sequence alignment and phylogenetic analyses showed that KvTIP3 shared 65%–82% homology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Downregulation of several TIPs in P. nuttalliana by the NaCl treatment may also have important consequences to water homeostasis by regulating water fluxes across the tonoplast. Several studies revealed that TIP aquaporins, which are primarily located in the vacuolar membrane (Maurel et al, 2008), play important roles under salt stress (Afzal et al, 2016;Liu X. et al, 2020). In addition to the intracellular water movement, TIPs are involved in transporting small solutes and gases (Nozaki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of several TIPs in P. nuttalliana by the NaCl treatment may also have important consequences to water homeostasis by regulating water fluxes across the tonoplast. Several studies revealed that TIP aquaporins, which are primarily located in the vacuolar membrane (Maurel et al, 2008), play important roles under salt stress (Afzal et al, 2016;Liu X. et al, 2020). In addition to the intracellular water movement, TIPs are involved in transporting small solutes and gases (Nozaki et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Kosteletzkya pentacarpos L. (seashore mallow), formerly known as Kosteletzkya virginica (Liu et al, 2020(Liu et al, , 2021, is a perennial halophyte belonging to the Malva genus of the Malvaceae family. It is naturally distributed on the salt marshy coasts of eastern United States, and is commercially used for the production of oil (Ruan et al, 2008), feed (Sun et al, 2019), medicines (Bai et al, 2015), and beauty products (Qin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The heat shock protein gene KvHSP70 is sensitive to NaCl stress and significantly improves the salinity tolerance of transgenic tobacco plants (Tang et al, 2020). Subsequently, the salinity stress-sensitive genes cloned from K. pentacarpos, such as the chloroplast small heat shock protein gene KvHSP26 and the tonoplast intrinsic protein gene KvTIP3, are potential candidates for molecular plant breeding (Liu et al, 2020(Liu et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%